Conduct problems co-occur with hyperactivity in children with language impairment: A longitudinal study from childhood to adolescence. (June 2016) - Pickles, Andrew; Durkin, Kevin; Mok, Pearl LH; Toseeb, Umar; Conti-Ramsden, Gina
Background: Language impairment is a common developmental disorder which is frequently associated with externalising problems. In this study, we investigate for the first time, joint trajectories of conduct problems and hyperactivity in children with language impairment from childhood to adolescence. We determine patterns of co-occurrence of symptoms and identify specific risk and protective factors. Methods: We develop a trajectory grouping method to examine simultaneously the conduct and hyperactivity problem scores of 164 children with language impairment at 7, 8, 11 and 16 years of age. Results: We identified five groups of children with distinct trajectories of symptoms. Three trajectory groups all had different conduct/hyperactivity problems: a persistent problems group (15%), an adolescent-onset group (24%) and a childhood-limited group (17%). There were two trajectory groups that did not show conduct problems. Conclusions: Conduct problems always co-occurred with hyperactivity in children with language impairment regardless of differences in the onset of symptoms (childhood versus adolescence) or their persistence (persistent versus childhood limited). Reading difficulties were strongly associated with mixed conduct/hyperactivity problems that started early (childhood) and continued into adolescence (the persistent trajectory group). Prosocial behaviours were found to be protective against conduct problems.